Diffusion and perfusion MRI of the lung and mediastinum - Henzler, Thomas; Schmid-Bindert, Gerald; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2010)
With ongoing technical improvements such as multichannel MRI, systems with powerful gradients as well as the development of innovative pulse sequence techniques implementing parallel imaging, MRI has now entered the stage of a radiation-free alternative to computed tomography (CT) for chest imaging in clinical practice. Whereas in the past MRI of the lung was focused on morphological aspects, current MRI techniques also enable functional imaging of the lung allowing for a comprehensive assessment of lung disease in a single MRI exam. Perfusion imaging can be used for the visualization of regional pulmonary perfusion in patients with different lung diseases such as lung cancer, chronic obstructive lung disease, pulmonary embolism or for the prediction of postoperative lung function in lung cancer patients. Over the past years diffusion-weighted MR imaging (DW-MRI) of the thorax has become feasible with a significant reduction of the acquisition time, thus minimizing artifacts from respiratory and cardiac motion. In chest imaging, DW-MRI has been mainly suggested for the characterization of lung cancer, lymph nodes and pulmonary metastases. In this review article recent MR perfusion and diffusion techniques of the lung and mediastinum as well as their clinical applications are reviewed.
Gesehen am 19.04.2023